Nguyên nhân và quy luật của thời tiết mưa lớn, "Mưa lớn trái mùa" vùng Bắc Trung Bộ (giai đoạn 1987-2006) - Vân, Nguyễn Khanh; Thủy, Đỗ Lệ (Vietnam Journal of Earth Sciences, 2009)
Causes and occurring frequency of heavy rain, “unusual heavy rain” in North Central of Vietnam (period 1987-2006) ...